Influence of Data Properties on Animated Maps - Lobben, Amy (Annals of the Association of American Geographers, 2008)
The effects of media and data properties on different methods of cartographic animation are unclear. This is due partially to the focus of previous research as well as the general lack of a conceptual framework for animation. Many researchers have discussed methods of visualizing 3-D and 4-D spatial data through cartographic animations but have not sufficiently identified the effects that visualization methods and data properties exert on the resulting products. Some results support the use of animations; others are inconclusive or unsupportive. Modality effects do not necessarily function as the primary mediator. As a result, media comparisons alone are not fully informative as so many other factors affect spatial data visualization "effectiveness." The research presented here is not just media comparison research, although two types of media are included: animation and static representations. This research is grounded in the developing conceptual framework of animation, which includes typologies of animation based on construction and delivery and on data properties (location, time, and attribute). The investigation focused on identifying the potential impact of data properties on subject responses and learning from different visualization methods. The results partially support the conceptual congruence hypothesis that dynamic data are more effectively displayed through dynamic media. However, the results also indicate that the data properties exert their own influence and that influence may be mediated, but not dependent, on the visualization method. Moreover, results support the developing conceptual framework and typology of animation that includes categorization of animation based on data properties or dimensions (location, time, attribute) and their dynamic or static nature.